2018
DOI: 10.1097/jom.0000000000001313
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Physiological Performance Determinants of a Firefighting Simulation Test

Abstract: Firefighter simulation test performance is associated with absolute cardiorespiratory fitness and fat mass. Fitter and leaner individuals perform the task more quickly. Work-based interventions should enhance these attributes to promote safe and effective operational performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…One possible explanation for these differences is that the present analysis employed a case‐control analytic method while a number of papers included in the Jalilian meta‐analysis compared firefighter incidence rates with general population incidence rates 6 . As indicated earlier, this latter approach can be more susceptible to underestimating true risk given the healthy worker effect 24,32 . Of note, nine of the 29 cancer incidence studies included in the Jalilian meta‐analysis calculations, 6 including the initial Florida analysis, 19 employed national or regional comparators in their SIR calculations (see Table S5) 6 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One possible explanation for these differences is that the present analysis employed a case‐control analytic method while a number of papers included in the Jalilian meta‐analysis compared firefighter incidence rates with general population incidence rates 6 . As indicated earlier, this latter approach can be more susceptible to underestimating true risk given the healthy worker effect 24,32 . Of note, nine of the 29 cancer incidence studies included in the Jalilian meta‐analysis calculations, 6 including the initial Florida analysis, 19 employed national or regional comparators in their SIR calculations (see Table S5) 6 …”
Section: Discussionmentioning
confidence: 98%
“…6 As indicated earlier, this latter approach can be more susceptible to underestimating true risk given the healthy worker effect. 24,32 Of note, nine of the 29 cancer incidence studies included in the Jalilian metaanalysis calculations, 6 including the initial Florida analysis, 19 employed national or regional comparators in their SIR calculations (see Table S5). 6 The present analysis found a strong risk of thyroid cancer in male and female firefighters.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…For example, aerobic capacity is an important contributing factor of performance on many firefighting tasks, particularly those that involve fire suppression . Firefighters with higher aerobic capacity and lower fat mass perform job tasks faster, and with increased efficiency while working with their self‐contained breathing apparatus . Therefore, exercise could be implemented to improve aerobic capacity which could lead to improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that firefighters who had lower VO 2 max scores were more likely to sustain an injury [ 4 ]. Another study found that those who had higher VO 2 max scores performed better on a firefighting simulation test [ 16 ]. Both studies indicated that firefighters with a better VO 2 max had better outcomes, whether that be injury occurrence or performance.…”
Section: Discussionmentioning
confidence: 99%